PENGARUH PROJECT BASED LEARNING TERHADAP MOTIVASI BELAJAR, KREATIVITAS, KEMAMPUAN BERPIKIR KRITIS, DAN KEMAMPUAN KOGNITIF SISWA PADA PEMBELAJARAN BIOLOGI - Insyasiska, Dewi; Zubaidah, Siti; Susilo, Herawati (Jurnal Pendidikan Biologi, 2015)
This research aims to determine the effect of  Project Based Learning to increase student’s motivation, creativity, critical thinking and cognitive abilities in learning biology. This quasi-experimental research design was "The Non Equivalent pretest-posttest control group design". Based on further testing of LSD showed that the project based learning can influence students 'motivation is higher by 14%, a 31.1% increase students' creativity, critical thinking skills increased by 34% and the cognitive abilities of students also increased 28.9% from the learning that is given without project. Project based learning motivates students to learn independently find their own information from various sources, such as a team of experts, environment, media and internet. Students are motivated to cooperate with the team to generate creative ideas that then manifested in a product. Learning project trained to make students think critically about the contextual issues relating to biological materials through the themes they choose, so as to increase students' cognitive abilities from analysis, synthesis, evaluation, and creation.